PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING PADA MATERI PROTISTA UNTUK SISWA SMA KELAS X - Nurami Wika Syafrida; Fitra Suzanti; Riki Apriyandi Putra (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This research and development (research and development) aims to determine the quality of the development of discovery learning-based e-modules on protist material. The development method used in this study is the ADDIE model (analysis, design, development, implementation, and evaluation). The quality of the e-module developed was seen from the assessment of the team of experts (material experts, media experts, and pedagogic experts), learning practitioners and students. The assessment instruments used were validation sheets, practitioner sheets, and student response sheets. The results of the expert team's assessment got a score of 4.47 with a very valid category. The results of the assessment from learning practitioners obtained a score of 84.71% in the very practical category. Furthermore, the results of student responses to the use of discovery learning -based e-modules get a score of 3.64 in the good category. Based on the results of this assessment, it can be concluded that the discovery learning-based e-module developed by researchers is a quality product and is suitable for use in the learning process.